A Nietzschean Odyssey: On the Trans-valuation of Values. (January 2019) - Rathore, Aakash Singh
This article places Friedrich Nietzsche's call to trans-valuate values into a wider historical (and disciplinary) panorama, hearkening back to ethical orientations within both the Archaic and the Attic Greek world with respect to the unity of the virtues. It is argued that the unity of cognitive and bodily (i.e., erotic, athletic) excellence, so central to the Greek world, and culminating in Aristotle's ethics, functioned inchoately as the measure according to which Nietzsche evaluated values. Extrapolating from the phenomenon of rival perceptions regarding the paradigmatic sculpture of Rodin's The Thinker—both from the time of its creation and in our own day—the article concludes by suggesting that moral philosophies alienated from the demand of the unity of physical and cognitive virtues might indeed be subject to the devastating critique that Nietzsche had advanced. The egalitarian nature of these values and this critique, however, remains an open question.